Modelling, control and robustness analysis of a 2-DoF exoskeleton-upper limb system. (17th April 2022) - Bembli, Sana; Haddad, Nahla Khraief; Belghith, Safya
This paper presents a new adaptive gain terminal sliding mode with gravity compensation control of an exoskeleton-upper limb system. The treated system is a two-degree-of-freedom robot (2-DoF) in interaction with an upper limb used for rehabilitation. The objective is to control the flexion/extension movement of the shoulder and the elbow in presence of matched disturbances. First, the modelling, the control and the stability study of the considered system using different laws were made. Next, a comparison study between these tested algorithms was done based on Monte Carlo robustness analysis method. Finally, the performance and the effectiveness of the adaptive gain terminal sliding mode algorithm combined with the Gravity Compensation in presence of uncertainties are provided by simulation results.